Irvine’s inner circle - Friedman, Grant M (2020)
There is an exponentially increasing population seeking and enrolling in higher education. There is a relatively finite amount of established institutions and an ever expanding population on this earth. Historical urbanization patterns demonstrate that higher education raises housing demand, and research shows that over time quality education systematically raises value/prices of the local real estate market. Tax advantages of real estate ownership are explained. Through an explanation of how appraisals are executed, an understanding of how value is measured in real estate is developed. The main appraisal method actualized in this research is the income method. This research uses publicly available market data to illustrate the opportunities inside University of California, Irvine’s student rental market through quantitative and qualitative methods. Decades of market data is prepensed and examined to provide a resolved understanding of public market metrics. Evaluation forecasts regarding profitability now and in the future are constructed, by paralleling adjacent industry rents and year over year increases. Through conservative analytical underwriting, and corporate parrelling of rates, the publicly available rental market is evaluated to exemplify the possible returns and quasi-rents. Through referencing city, county and state averages, the investment opportunity is brought to life. Risk is respected in its relationship to quasi-rent opportunities. All in all, this paper seeks to understand the profitability of a person that positions themselves next to a pre-developed, growing university, while copying a flourishing private corporate investment system. The overall findings of this research prove that a dynamic, calculated investor could see returns well above city, county and state averages if quasi-rents are captured.